The Impact of Modern Strategies for Crisis Management on The Performance: Case Study of Sonelgaz Company-Laghouat - Amal Metabis; Aicha Soufrani; Asia Benahmed (Dirassat Journal Economic Issue, 2022)
crisis management is one of oldies and modern subject; the organizations was and still is the scene of the problem’s colors, At present the organizations are working in order to resist using the strategies , so study aimed to learn about the modern strategies for crisis management (teams and democratic participation strategy  , reserve mobilization strategy , escalation strategy, strategy to divert the crisis and containment ) in institutions and their impact on the performance from the standpoint of personnel institution SONELGAZ, which is designed to identify the study have been using SPSS statistical software to test hypotheses and the study concluded that there is effect of crisis management strategies) teams and democratic participation strategy, reserve mobilization strategy (in the performance of individuals working at the level of significance α ≤0.05.